CROWDS MANAGEMENT IN INDONESIAN FOOTBALL EVENT CASE STUDY : POLICING MANAGEMENT - Andry Wibowo (Fakultas Ekonomi Universitas Negeri Jakarta, 2017)
Crowds become an important issue in policing research and practice.Crowds phenomena become a challenge for police management to make an order, safety and security in public issue.Crowds in football event bring some problemsrelated to problem of order, safety and security and become a developing research object in football industry.This paper describe crowds problems in sport could transforms into identity problem.Problem orientated policing is a modern thought who give police to understand root of causes from social problem. This paper describe and explore condition from group of crowds Viking (Persib) and Jakmania (Persija) in Indonesia whohave an identity conflict among them and have been distrubing public order, safety and security for almost to decade until now. Relate to those problems this paper alsodescribe and explorw how Indonesian police management handle this problem as part of a policing models. Keywords: crowds; incident drivent policing; identity conflict; problem oriented policing; crowds cycle